FACTORS AFFECTING CONTINUOUS INTEREST IN USING THE MOBILE APPLICATION BPJSTKU (SURVEY: WORKERS OF PT MITSUBISHI MOTORS KRAMA YUDHA INDONESIA, CIKARANG) - Malada, Lazuardi Putra (Dinasti International Journal of Digital Business Management, 2022)
This study aims to determine the factors that influence the continuing interest in using the BPJSTKU mobile application, at the workforce of PT Mitsubishi Motors Krama Yudha Indonesia, Cikarang. The research design uses a quantitative approach and the type of research is causal research. The research method uses a survey. The research population at PT Mitsubishi Motors Krama Yudha Indonesia is 3,107 workers. The sampling technique was purposive sampling with a total sample of 210 people. Collecting data in the form of a questionnaire. The research data were analyzed using the SEM method with data processing through the SmartPLS 3.0 application. The results of the study indicate that the factors that influence continued interest in using the BPJSTKU mobile application are system quality, information quality, social norms, which are mediated by the variables of satisfaction and perceived usefulness. System quality and information quality partially have a positive and significant effect on satisfaction and perceived usefulness. Then, social norms, satisfaction, and perceived usefulness partially have a positive and significant effect on continued interest in using the BPJSTKU mobile application.